Indonesia's Hedging Strategy Amid US–China Rivalry in the Indo-Pacific - Muhammad Thomi Arshan; Salsabila Jihan Utami (International Journal Labs, 2026)
The strategic rivalry between the United States and China in the Indo-Pacific creates significant structural pressure for Indonesia as a key middle power and ASEAN leader. However, Indonesia remains underexplored in hedging strategy studies compared to other Southeast Asian countries. Moreover, the 2019–2024 period—marked by AUKUS, IPEF, Indonesia’s G20 presidency and ASEAN chairmanship, and rising tensions in the Natuna waters—has not been systematically analyzed. An additional gap lies in internal institutional incoherence, whereby key state actors do not consistently present aligned strategic signals. This article examines how Indonesia operationalizes its hedging strategy in response to the US–China rivalry during 2019–2024 across three interrelated dimensions: diplomatic-institutional, economic, and security. Data were collected through document analysis, qualitative content analysis, and process tracing. The findings show that Indonesia consistently pursued soft hedging that preserved its foreign policy autonomy. The article advances three theoretical contributions: identifying institutional incoherence as a new variable that erodes hedging credibility; demonstrating that Wilkins’s security–economic disconnect more accurately captures Indonesia’s structural dilemma than conventional small-state hedging frameworks; and arguing that, for middle powers such as Indonesia, hedging functions not merely as a survival strategy but as a self-reinforcing leadership strategy.